Evaluasi Pemberian Tunjangan Kinerja Studi Di Balai Teknik Kesehatan Lingkungan Dan Pengendalian Penyakit Kelas I Manado - Kejeh, Marviel Mario (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This type of research is descriptive evaluative. The purpose of this study was to determine the effectiveness, leveling and responsiveness implementation of performance allowances of civil servants in the Manado Class I Environmental Health Engineering Center and Disease Control. The results showed that the implementation of monitoring and evaluation at the Manado Class I Environmental Health Engineering Center and Disease Control has been running effectively even though there are still various shortcomings in its implementation including the use of fingerprint attendance. Leveling the amount of performance received has been carried out in accordance with established procedures but In the field, the researchers found that determining the grade / class position is still not in accordance with the workload of some civil servants, the responsiveness of employees has been very good it can be seen from the level of attendance and productivity of civil servantsKeywords: Evaluation, Performance Allowances